Conodont size, trophic level, and the evolution of platform elements. Issue 3 (18th June 2019) - Ginot, Samuel; Goudemand, Nicolas
Abstract: Conodonts are among the first vertebrates to have evolved mineralized tooth-like structures. Among these, the so-called P1 elements are known to have been used to break down food and display a wide variety of morphologies. In particular, the repeated independent evolution of platform-like P1 elements have been suggested to correspond to similar functional constraints linked to diet. To test this hypothesis of convergence, we measured size (as element length) for various conodont taxa and used it as a proxy for trophic level. We then tested the correlation between size and platform presence/absence, both on raw data and in a phylogenetic context. Retaining or excluding the platform traits from the character matrix has limited impact on the resulting phylogeny. Contrary to platform presence/absence, size shows no phylogenetic signal. Using the raw data, size and platform presence appear positively correlated. That correlation, however, is no longer significant if one corrects for the phylogeny. We conclude that platform presence cannot be explained by an enlargement of the conodont element, be it via a trophic-level change or developmental constraints. This suggests that conodonts as a whole, and in particular platform-bearing conodonts, were an ecologically diverse group and that the various known platform types are likely to reflect different, rather than convergent, ecological niches.